PERENCANAAN NORMALISASI SUNGAI BLUKAR KABUPATEN KENDAL - Erick Chendratama; I Putu Dian Arie Wibawa; Sriyana Sriyana; Sumbogo Pranoto (Jurnal Karya Teknik Sipil, 2013)
Changes in land use in the Blukar watershed impact on the amount of surface runoff that flows directly into the river. The result is erosion in the upstream areas, while sedimentation occurs in downstream areas. Sedimentation make river capacity is reduced so that the puddle caused by flooding can not be avoided. The purpose of this paper is to reduce the puddle caused by flooding of Blukar river by providing designs of river normalization and conservation. The method used are the analysis of the average maximum rainfall using Polygon Thiesen method, analysis of rainfall intensity using Mononobe formula, flood discharge analysis with Rational method, FSR Java-Sumatra, Haspers, Weduwen, HSS Gama I, HEC-HMS (computer program) and Passing Capacity, channel cross-sectional analysis with the aid of a computer program HEC-RAS, foundation and slope stability analysis using Shield and Fellenius formula. The study results showed that of the various method of flood discharge analysis conducted, flood discharge plan selected by FSR Java-Sumatra method with return period of 25 years at 210.6705 m3/sec, sectional repairs done from STA 0+000 - STA 22+500 with 22.5 km long with the help of HEC-RAS which channel base width of 35 m, the embankment slope 1:1.5, the water level varies, and surveillance by 0.8 m high. From the analysis of HEC-RAS was found that the dimensions above approximate can reduce the floodwaters as high as 1.71 m. Meanwhile for excavation, the total volume of channel excavation is 2,471,904.5 m3 with details of 378,615 m3 used as material embankment and 2,093,289.5 m3 discharged to disposal area. Furthermore, in order to obtain optimal performance results of Blukar watershed flood management, need to follow up by involving various stakeholders.